2014
DOI: 10.5056/jnm.2014.20.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Enteric Motor Neurons in the Gastric Fundus of Mice With Reduced Intramuscular Interstitial Cells of Cajal

Abstract: Background/AimsInterstitial cells of Cajal (ICC) play important functions in motor activity of the gastrointestinal tract. The role of ICC as pacemakers is well established, however their participation in neurotransmission is controversial. Studies using mutant animals that lack ICC have yielded variable conclusions on their importance in enteric motor responses. The purpose of this study was to:(1) clarify the role of intramuscular ICC (ICC-IM) in gastric motor-neurotransmission and (2) ConclusionsThis study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Second, we used corpus (proximal glandular stomach) area of rat stomach for the quantitative (morphological) or molecular experiment instead of forestomach. Although many previous studies [22, 38, 44, 59] reported about the experiment of gastric relaxation in murine, there was no definite mention about the precise region of fundus in the murine stomach. The stomach of the rat is divided into the forestomach (pars proventricularis) and glandular stomach (corpus or pars glandularis), which is different from human.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we used corpus (proximal glandular stomach) area of rat stomach for the quantitative (morphological) or molecular experiment instead of forestomach. Although many previous studies [22, 38, 44, 59] reported about the experiment of gastric relaxation in murine, there was no definite mention about the precise region of fundus in the murine stomach. The stomach of the rat is divided into the forestomach (pars proventricularis) and glandular stomach (corpus or pars glandularis), which is different from human.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sanders et al . revealed that the inhibitory responses were absent or reduced when ICC-IM were partially or completely lost, providing evidence for the role of ICC-IM in mediating inhibitory neurotransmission in the gastric fundus of W/W V mice [22]. Furthermore, decrease or loss of ICC in the human gut was frequently observed in the diabetic gastroenteropathy [23] or slow transit constipation [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…; Sanders et al . a ). ICC‐DMP also appear to contribute to neurokinin responses initiated by peptidergic motor neurons because they express NK1 receptors and internalize these receptors during nerve stimulation (Iino et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a re-evaluation of this question we found that the lesion in ICC-IM varies to some extent in different animals. When ICC-IM were greatly reduced, nitrergic responses were greatly reduced, but when clusters of ICC-IM remained, nitrergic responses were observed12. A recent study using cell-specific inducible Cre recombinase (iCre) to knock down soluble guanylate cyclase (sGC) found that nitrergic responses were affected only to a minor extent when the lesion in sGC was directed at ICC and only partially decreased when sGC was knocked down in smooth muscle cells19.…”
Section: Discussionmentioning
confidence: 99%